Applying for, reviewing and funding public health research in Germany and beyond. Issue 1 (December 2016) - Gerhardus, Ansgar; Becher, Heiko; Groenewegen, Peter; Mansmann, Ulrich; Meyer, Thorsten; Pfaff, Holger; Puhan, Milo; Razum, Oliver; Rehfuess, Eva; Sauerborn, Rainer; Strech, Daniel; Wissing, Frank; et al.
Abstract Public health research is complex, involves various disciplines, epistemological perspectives and methods, and is rarely conducted in a controlled setting. Often, the added value of a research project lies in its inter- or trans-disciplinary interaction, reflecting the complexity of the research questions at hand. This creates specific challenges when writing and reviewing public health research grant applications. Therefore, the German Research Foundation (DFG), the largest independent research funding organization in Germany, organized a round table to discuss the process of writing, reviewing and funding public health research. The aim was to analyse the challenges of writing, reviewing and granting scientific public health projects and to improve the situation by offering guidance to applicants, reviewers and funding organizations. The DFG round table discussion brought together national and international public health researchers and representatives of funding organizations. Based on their presentations and discussions, a core group of the participants (the authors) wrote a first draft on the challenges of writing and reviewing public health research proposals and on possible solutions. Comments were discussed in the group of authors until consensus was reached. Public health research demands an epistemological openness and the integration of a broad range of specific skills and expertise. Applicants need to explicitly refer to theories as well as to methodological and ethical standards and elaborate on why certain combinations of theories and methods are required. Simultaneously, they must acknowledge and meet the practical and ethical challenges of conducting research in complex real life settings. Reviewers need to make the rationale for their judgments transparent, refer to the corresponding standards and be explicit about any limitations in their expertise towards the review boards. Grant review boards, funding organizations and research ethics committees need to be aware of the specific conditions of public health research, provide adequate guidance to applicants and reviewers, and ensure that processes and the expertise involved adequately reflect the topic under review.